Preparation method and application of active element-doped sericin mineralized particles loaded with EGCG nanocomposite material

By using silk gum nanoparticles as templates, combined with chemical precipitation method, synthesis of copper pyrine modified hydroxylite nanoparticles combined with chemical precipitation method, and loaded EGCG function coating to form the ore mineralized granules EGCG nano -nano Composite materials solve the problem of complexity and single function of active elements in existing technologies, and realize the preparation of multifunctional biomedical materials.

CN118512651BActive Publication Date: 2025-01-28STOMATOLOGICAL HOSPITAL AFFILIATED TO SOUTHWEST MEDICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410401523.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-01-28
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

The method of synthesizing active elements doping hydroxyapatite in the prior art is complex. The obtained nanoparticles only contain calcium and phosphorus elements, which are not enough to fully simulate the internal environment after degradation. The biological function is single and multiple biological functions cannot be integrated.

Method used

Use filament protein as a template, prepare silk gum particles (SE NPS) through a homogeneous mechanism, and then use SE NPS to synthesize copper hydroxylite nanoparticles with SE NPS as a biological template. Functional coating PEI/EGCG, forming silk gel mineralized particle load EGCG nano -composite materials.

Benefits of technology

A variety of functional functions of nano -composite materials have been achieved, with a variety of biological functions that remove active oxygen, regulate macrophages, promote blood vessel production and bone repair, break the single nature of biomass materials, and have a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118512651B_ABST
    Figure CN118512651B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an active element-doped sericin mineralized particle-loaded EGCG nanocomposite material. The method adopted by the invention is simple and easy to implement, has high yield, no toxic byproducts, and a non-toxic and harmless preparation process. The synthesized copper strontium-modified hydroxyapatite has controllable size and good degradation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a preparation method and application of an active element-doped sericin mineralized particle-loaded EGCG nanocomposite material. Background Art

[0002] Natural bone is mainly composed of two parts: inorganic components and organic components. The inorganic component is mainly low-crystalline hydroxyapatite (HA), while the organic component is mainly composed of proteins and polysaccharides. Compared with natural bone materials, bionic materials prepared in vitro have the advantages of sufficient sources and low immunogenicity. There are many bone materials that select calcium and phosphorus as the main components to simulate natural bone components, and even use in vitro mineralization methods to simulate the smallest structural unit of natural bone, which can have a good osteoinduction effect. However, in clinical needs, the repair of bone defects should not only consider the bone regeneration performance, but also the causes of bone defects and the need for postoperative repair. It is also very important to have targeted additional functions. In addition to the main components of calcium and phosphorus, natural bones also contain a variety of trace elements, such as copper (Cu), strontium (Sr), magnesium (Mg), etc. Among them, copper is an essential trace element in the growth and development of the human body. It plays a vital role in angiogenesis by promoting the proliferation of human endothelial cells and stimulating the secretion of vascular endothelial growth factor (VEGF). In addition, strontium-modified hydroxyapatite can significantly promote angiogenesis and bone regeneration. Co-doping of multiple ions can further enhance the biological properties of hydroxyapatite. Many studies have shown that Sr or Cu combined with hydroxyapatite may promote angiogenesis, remove metabolic waste, and transport oxygen and nutrients to promote subsequent new bone formation. It can be seen that the introduction of trace elements can not only enhance the osteogenic induction ability of the material, but also achieve a variety of additional biological functions. However, the method of synthesizing active element-doped hydroxyapatite in the prior art is complicated and cumbersome, and the obtained nanoparticles only contain calcium and phosphorus elements, which are not enough to completely simulate the in vivo environment after degradation. Bone repair is not a single repair process in clinical practice, but is accompanied by a vascularization process, thereby promoting bone repair and regeneration.

[0003] Among various multifunctional nanocarriers, protein nanocarriers have attracted extensive attention due to their self-assembly behavior, excellent biocompatibility, and biodegradability. Silk is a natural protein secreted by silkworms and has attracted increasing attention in recent biomedical applications. Sericin is one of the main components of silk, wrapped in the outer layer of silk fibers, rich in acidic amino acids such as aspartic acid and glutamic acid, and contains many polar side chains of hydroxyl, carboxyl, and amino groups. These acidic amino acids have been shown to supersaturate calcium ions in metastable solutions and provide "nucleation sites". Due to the hydrophilicity of sericin, it is difficult to maintain a stable structure in water. Sericin nanoparticles (Se NPs) can be prepared by crosslinking or copolymerization and have excellent biocompatibility and biodegradability. The formation of Se NPs is promoted by their internal amino acids, which are easy to crosslink or copolymerize and can also serve as nucleation sites for hydroxyapatite.

[0004] Epigallocatechin-3-gallate (EGCG) is a naturally occurring polyphenol with good scavenging ability for reactive oxygen species (ROS). Due to its pharmacological activities such as antioxidant and anti-inflammatory, EGCG has been shown in several studies to have the ability to inhibit M1 macrophage polarization, promote M2 macrophage polarization, promote skull repair and wound healing. However, the instability and low bioavailability of EGCG often limit its clinical application. In a weakly alkaline environment, EGCG exhibits strong adhesion to the surface of materials through oxidative self-polymerization. In addition, EGCG can be cross-linked with the widely used amino-rich coating polymer polyethyleneimine (PEI) through Schiff base reaction and Michael addition.

[0005] Periodontitis is a chronic inflammatory disease caused by dental plaque, characterized by persistent inflammation, persistent activation of osteoclasts, irreversible loss of alveolar bone, and ultimately tooth loss. Under the continuous stimulation of bacteria and lipopolysaccharide (LPS), overactivated macrophages (M1-type) and neutrophils produce excessive inflammatory mediators and reactive oxygen species, leading to oxidative stress, hindering the osteogenic differentiation of host stem cells (such as periodontal ligament stem cells), activating osteoclasts and secreting matrix metalloproteinases (MMPs), and aggravating periodontal tissue damage and attachment loss. Traditional treatment measures are still deep periodontal pocket scraping, periodontal flap surgery, and membrane gingival therapy. However, due to the influence of periodontal anatomical structure, the effect of scraping is limited, and it cannot completely remove plaque, inhibit inflammation and alveolar bone resorption. In addition, the immune system and the skeletal system share many cytokines, receptors, signaling molecules, and transcription factors. It can be seen that immune cells play a key role in bone homeostasis.

[0006] Therefore, the development of multifunctional biomaterials that can not only scavenge ROS and regulate immune responses, but also efficiently promote vascularized bone regeneration is of great significance for solving the clinical treatment problems of periodontitis.

[0007] In the prior art, the invention patent with application number CN201510149465.8 and publication date of August 12, 2015, entitled "A method for preparing hydroxyapatite / sericin hybrid microcapsules", discloses a method for preparing hydroxyapatite / sericin hybrid microcapsules, wherein the microcapsules are composed of a hydroxyapatite layer on the surface and a sericin capsule wall layer. However, the technical solution first denatures the sericin with alcohol, and the shape of the sericin is not controlled during this process, so the mechanical properties of the formed hybrid microcapsules are poor. Moreover, the degradation products of the hydroxyapatite / sericin hybrid microcapsules only contain calcium and phosphorus elements, and have a single biological function.

[0008] In the prior art, the invention patent with application number 201810507821.2 and publication date of May 24, 2018, entitled "A natural sericin microsphere wrapped by a metal organic coordination polymer and its preparation method and application", discloses a sericin microsphere and its preparation method, and successfully prepares sericin microspheres with regular morphology, uniform particle size and good dispersibility by combining oil-in-water emulsification method with chemical crosslinking method. The method is simple and easy to implement, with high yield, no toxic byproducts, and the preparation process is non-toxic and harmless. The obtained sericin microspheres have a smooth surface and controllable size (5-100μm). With fluorescent properties, the microspheres can effectively carry drugs and cells based on the good biocompatibility and cell adhesion of sericin itself. However, the sericin microspheres prepared by this technology have a single function and only have the function of the loaded drugs. In addition, the particle size of the microspheres synthesized by the above preparation technology is about 5-100μm, which is relatively large. This natural sericin microsphere only has the anti-inflammatory function of the loaded drugs, such as tannic acid, anthocyanin, catechin, gallic acid, arbutin or catechol group-modified polymers, and still cannot integrate multiple biological functions.

[0009] In view of the above technical problems, the present invention provides a preparation method and application of an active element-doped sericin mineralized particle-loaded EGCG nanocomposite material having immunomodulatory, angiogenic and osteogenic functions. Summary of the invention

[0010] The purpose of the present invention is to provide a preparation method and application of an active element-doped sericin mineralized particle-loaded EGCG nanocomposite material having immunomodulatory, angiogenic and osteogenic functions.

[0011] The object of the present invention is achieved in that:

[0012] Step 1. extracting sericin to obtain sericin powder, and storing it at 4°C for later use;

[0013] Step 2. Prepare a 10 wt% sericin solution: weigh 0.9-1.1 g of sericin prepared in step 1 and dissolve it in 9-11 mL of deionized water to obtain a sericin solution for later use;

[0014] Step 3. Prepare the oil phase solution: add 2 mL of span80 into 98 mL of peanut oil and stir evenly using a high-speed homogenizer to obtain an oil phase emulsion;

[0015] Step 4. Add the sericin solution in step 2 dropwise into the oil phase emulsion in step 3 being homogenized, and homogenize at 4000 rpm for 20 minutes to obtain a sericin mixed emulsion;

[0016] Step 5. Add 2 mL of glutaraldehyde crosslinking agent (25%) to the mixed emulsion obtained in step 4 and stir at 150 rpm for 2 hours to fully crosslink the Se NPs;

[0017] Step 6. Suspend the solution obtained in step 5 into 300 mL of acetone solution and stir overnight to allow the particles to fully solidify;

[0018] Step 7. After the mixed solution in step 6 is separated, the white suspension layer is sucked out with a pipette, transferred to a new container, and washed with acetone for 3 times to obtain solidified sericin nanoparticles Se NPs; the results are shown in FIG. Figure 2 shown.

[0019] Step 8. Weigh 100 mg of the sericin nanoparticles Se NPs obtained in step 7, place in 100 mL of deionized water, stir evenly, add CaCl2, SrCl2 and CuCl2, stir at 150 rpm for 8 hours, maintain the temperature at 37°C, and make the metal ions (Ca 2+ , Sr. 2+ , Cu 2+ ) fully combined with Se NPs;

[0020] Step 9. After the reaction in step 8 is completed, filter paper is used to filter to remove excess unbound ions, and the precipitate is resuspended in 100 mL, and 0.018-0.030 mol of Na3PO4 powder is added, and the pH is adjusted to 8.0 using sodium hydroxide solution. Stir at 150 rpm for 8 hours, age, filter, and wash to obtain sericin-copper strontium modified hydroxyapatite nanoparticles (Se-CuSrHANPs). The results are as follows Figure 3 shown.

[0021] Step 10. Prepare 20 mL of PEI / EGCG functional coating solution: 1 mg / mL EGCG and PEI dissolved in tris buffer solution were mixed in equal volumes to obtain a PEI / EGCG solution, wherein the concentration of the PEI solution was 2 mg / mL.

[0022] Step 11. The Se-CuSrHANPs obtained in step 9 were placed in the PEI / EGCG solution of step 10 and stirred at 37°C for 4 hours to fully cross-link the molecules. The unbound molecules were washed with deionized water and freeze-dried to obtain the sericin mineralized particles loaded with EGCG nanocomposite Se-CuSrHA@EGCG NPs. The results are shown in FIG. Figure 4 Shown

[0023] Step 12. Characterization of Se-CuSrHA@EGCG NPs: The molecular, structural and elemental compositions of Se-CuSrHA@EGCG NPs were detected by FTIR, XPS and EDS mapping. Figure 5 shown.

[0024] The specific operation of step 1 is as follows: weigh 9-11g of silkworm cocoons, cut them into pieces, wash them three times with deionized water, add them into 250mL of ultrapure water containing 2% w / v sodium carbonate, and heat and pressure at 120℃ for 30 minutes to remove silk fibroin. After completion, filter and collect the solution, centrifuge at 3000rpm for 5 minutes; further dialyze (MWCO: 3500Da) for 48 hours to remove impurities, and change the solution every 8 hours; after the dialysis is completed, obtain sericin powder by freeze drying and store it at 4℃ for future use.

[0025] The specific operation of step 8 is as follows: the amount of the CaCl2 powder is 0.024-0.040 mol, the amount of the SrCl2 powder is 0.003-0.005 mol and the amount of the CuCl2 powder is 0.003-0.005 mol.

[0026] An application of a sericin mineralized particle loaded with EGCG nanocomposite material, wherein the sericin mineralized particle loaded with EGCG nanocomposite material is applied to bone material.

[0027] The beneficial effects of the present invention are as follows: (1) the sericin used in the present invention is a natural protein with good biocompatibility and good stability after being solidified with acetone; (2) the present invention adopts a homogenizer to prepare Se NPs, which is simple and easy, has a high yield, no toxic byproducts, and the preparation process is non-toxic and harmless. The prepared nanoparticles have uniform size, and the particle size can be well controlled by changing the homogenization speed; (3) the present invention adopts a chemical precipitation method, uses Se NPs as a biological template to mineralize and synthesize copper strontium modified hydroxyapatite, and further loads an antioxidant functional coating (PEI / EGCG). The method is simple, the size is uniform with Se NPs, no high molecular polymer is used in the process, and the degradation performance is good; (4) with the doping mineralization and functional coating of metal ions, the nanoparticles are endowed with multiple biological functions such as scavenging reactive oxygen, regulating macrophage polarization, promoting angiogenesis and osteogenic repair, breaking the functional singleness of biomaterials. It has broad application prospects in the fields of tissue engineering, fluorescent tracing and drug carriers. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the preparation of the active element-doped sericin mineralized particles loaded with EGCG nanocomposite material of the present invention;

[0029] Figure 2 is a scanning electron microscope image of Se NPs of the present invention;

[0030] Figure 3 is a scanning electron microscope image of Se-CuSrHANPs of the present invention;

[0031] Figure 4 is a scanning electron microscopy image of Se-CuSrHA@EGCG NPs of the present invention;

[0032] Figure 5 These are the characterization detection diagrams of Se-CuSrHA@EGCG of the present invention: wherein, Figure A is the mapping spectrum of Se-CuSrHA@EGCG NPs, and Figures BG are the XPS analysis diagrams of Se-CuSrHA@EGCG.

[0033] Figure 6 Figure 1 is a graph showing the immune regulation ability of the blank control group, negative control group and Se-CuSrHA@EGCG NPs group in the examples of the present invention: Figure A, flow cytometry identification of the type of macrophage polarization (M1 macrophage surface marker (CD86), including M2 macrophage surface marker (CD206)); Figure B, immunofluorescence staining of the control group, negative control group and Se-CuSrHA@EGCG NPs group (M1 macrophage surface marker (iNOS), including M2 macrophage surface marker (CD206));

[0034] Figure 7 Figure 1 is a graph showing the angiogenesis-promoting ability of Se-CuSrHA@EGCG NPs in the embodiments of the present invention: Figure A, tubule formation assay; Figure B, scratch assay; Figure C, angiogenesis gene assay; Figure D, immunofluorescence staining assay (VEGF);

[0035] Figure 8 These are graphs showing the osteogenic ability of Se-CuSrHA@EGCG NPs in the examples of the present invention: Figure A, ALP and Alizarin Red staining; Figure B, osteogenic gene detection; Figure C, immunofluorescence staining experiment (RUNX2 and OPN). DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0037] Step 1. Extract sericin and obtain sericin powder, which is stored at 4°C for future use; weigh 10g of silkworm cocoons, cut them into pieces, wash them three times with deionized water, add them to 250mL of ultrapure water containing 2% w / v sodium carbonate, and heat and pressure at 120°C for 30 minutes to remove the silk fibroin. After completion, filter and collect the solution, centrifuge at 3000rpm for 5 minutes; further dialyze (MWCO: 3500Da) for 48 hours to remove impurities, and change the solution every 8 hours; after dialysis, obtain sericin powder by freeze drying, and store it at 4°C for future use

[0038] Step 2. Prepare a 10 wt% sericin solution: weigh 0.9 g of sericin prepared in step 1 and dissolve it in 9 mL of deionized water to obtain a sericin solution for later use;

[0039] Step 3. Prepare the oil phase solution: add 2 mL of span80 into 98 mL of peanut oil and stir evenly using a high-speed homogenizer to obtain an oil phase emulsion;

[0040] Step 4. Add the sericin solution in step 2 dropwise into the oil phase emulsion in step 3 being homogenized, and homogenize at 4000 rpm for 20 minutes to obtain a sericin mixed emulsion;

[0041] Step 5. Add 2 mL of glutaraldehyde crosslinking agent (25%) to the mixed emulsion obtained in step 4 and stir at 150 rpm for 2 hours to fully crosslink the Se NPs;

[0042] Step 6. The solution obtained in step 5 was suspended in 300 mL of acetone solution and stirred overnight to allow the particles to fully solidify;

[0043] Step 7. After the mixed solution in step 6 is separated, the white suspension layer is sucked out with a pipette, transferred to a new container, and washed with acetone for 3 times to obtain solidified sericin nanoparticles Se NPs; the results are shown in FIG. Figure 2As shown, the obtained sericin nanoparticles Se NPs have a particle size of about 40-50 nm and a smooth morphology.

[0044] Step 8. Weigh 100 mg of the sericin nanoparticles Se NPs obtained in step 7, place in 100 mL of deionized water, stir evenly, add CaCl2 (0.032 mol), SrCl2 (0.004 mol) and CuCl2 (0.004 mol), stir at 150 rpm for 8 hours, maintain the temperature at 37°C, and make the metal ions (Ca 2+ , Sr. 2+ , Cu 2+ ) fully combined with Se NPs;

[0045] Step 9. After the reaction in step 8 is completed, filter paper is used to remove excess unbound ions, and the precipitate is resuspended with 100 mL, and Na3PO4 (0.024 mol) is added. The pH is adjusted to 8.0 with sodium hydroxide solution. Stir at 150 rpm for 8 hours, age, filter, and wash to obtain sericin-copper strontium modified hydroxyapatite nanoparticles Se-CuSrHANPs. The results are as follows: Figure 3 As shown, the obtained sericin-copper strontium modified hydroxyapatite nanoparticles (Se-CuSrHANPs) have a particle size of about 80-100 nm, which is quite different from the particle size of Se-NPs, and a rough morphology, which indicates the formation of mineralization.

[0046] Step 10. Prepare 20 mL of PEI / EGCG functional coating solution: 1 mg / mL of EGCG and PEI (2 mg / mL) dissolved in tris buffer solution were mixed in equal volumes to obtain a PEI / EGCG solution.

[0047] Step 11. The Se-CuSrHANPs obtained in step 9 were placed in the PEI / EGCG solution of step 10 and stirred at 37°C for 4 hours to fully cross-link the molecules. The unbound molecules were washed with deionized water and freeze-dried to obtain the sericin mineralized particles loaded with EGCG nanocomposite Se-CuSrHA@EGCG NPs. The results are shown in FIG. Figure 4 As shown, the obtained sericin mineralized particles loaded with EGCG nanocomposite Se-CuSrHA@EGCG NPs had a particle size comparable to that of Se-CuSrHANPs, but a smoother morphology with a thin film visible, which may be attributed to the loading of the PEI / EGCG functional coating.

[0048] Step 12. Characterization and detection of sericin mineralized particles loaded with EGCG nanocomposite Se-CuSrHA@EGCG: The molecular, structural and elemental composition of Se-CuSrHA@EGCGNPs were detected by EDS mapping and XPS. Figure 5 As shown, the mapping spectrum shows that the obtained Se NPs loaded EGCG nanocomposite Se-CuSrHA@EGCG NPs are rich in elements such as C, N, P, Ca, Sr and Cu, and the FTIR spectrum. The chemical valence state of the elements in Se-CuSrHA@EGCG NPs was also analyzed by XPS spectrum. These results all indicate the successful construction of sericin mineralized particles loaded EGCG nanocomposite Se-CuSrHA@EGCG NPs.

[0049] Step 13. Immunomodulatory capacity detection: Detection by flow cytometry and immunofluorescence staining, such as Figure 6 As shown, the results showed that Se-CuSrHA@EGCG NPs had a good ability to inhibit the differentiation of M1 macrophages and promote the differentiation of M2 macrophages.

[0050] Macrophages (RAW264.7, 1×10 5 cells / mL) were inoculated into 6-well plates and cultured overnight with RMPI-1640 medium. They were polarized to M1 or M2 types by treatment with LPS or IL-4, respectively, which were represented as negative control groups. Next, Se-CuSrHA@EGCGNPs NPs (1 mg / mL) were immersed in RMPI-1640 medium for 48 hours to obtain Se-CuSrHA@EGCG extract. Macrophages were cultured for 48 hours with Se-CuSrHA@EGCG NPs extract (RMPI-1640 medium containing 10% FBS and 1% penicillin-streptomycin). Immunofluorescence staining, flow cytometry analysis and qRT-PCR were then performed.

[0051] Immunofluorescence: In vitro polarization of macrophages was qualitatively evaluated by IF staining by tracking the expression levels of mannose receptor (CD206) and inducible nitric oxide synthase (iNOS). RAW264.7 cells were seeded into confocal culture dishes (diameter = 15 mm). After overnight culture, the culture medium was enhanced with LPS or IL-4 to activate macrophages for 48 hours. The cells were cultured with the extract of Se-CuSrHA@EGCGNPs for 48 hours. Then, the cells were fixed with 4% paraformaldehyde for 30 minutes and blocked with 5% goat serum for 1.5 hours. The cells were incubated with the primary antibody iNOS (1:50, Proteintech) or CD206 (1:50, Proteintech) at 4°C overnight. Then the secondary antibody Alexa 647Conjugate (1:200, CellSignling Technology, USA) for 1 hour, and then the cell nuclei were stained with DAPI solution for 15 minutes, and the red fluorescence intensity was detected using a Leica confocal microscope (Germany) using Image J. Figure 6 As shown in B, the iNOS fluorescence intensity of the negative control was higher than that of the blank control group, which may be attributed to the stimulation of LPS. However, the Se-CuSrHA@EGCG group showed the opposite trend, with a significant decrease in iNOS fluorescence intensity, corresponding to a decrease in M1 macrophages. The CD206 fluorescence intensity of the negative control group was slightly stronger than that of the blank control group. In addition, the Se-CuSrHA@EGCG experimental group was stronger than the negative control group.

[0052] Flow cytometry analysis: The expression levels of blood leukocyte differentiation antigen 86 (CD86, M1 marker) and CD206 (M2 marker) were monitored to quantitatively evaluate the ratio of M1 and M2 macrophage polarization. Briefly, macrophages (1×10 5 The macrophages were then washed three times in cold PBS. Phycocyanin (APC)-bound CD86 and phycoerythrin (PE)-bound CD206 were used for M1 / M2 macrophage staining, respectively. After incubation for 20 minutes, the samples were analyzed by flow cytometry (ACEA NovoCyteTM, USA). Figure 6 A shows that the blank control group, negative control group and Se-CuSrHA@EGCG group were 7.91%, 49.7% and 8.97%, respectively. The M1 macrophage (CD86) count in the negative control group was more significant than that in the blank control group (7.91%). However, in the Se-CuSrHA@EGCG group, the number of M1 macrophages was significantly reduced (8.97%). The M2 macrophages (CD206) were 2.25%, 9.12% and 45.6% in the blank control group, negative control group and Se-CuSrHA@EGCG groups, respectively. The number of M2 macrophages was the largest, and the Se-CuSrHA@EGCG group was more able to stimulate the differentiation of M2 macrophages.

[0053] Step 14. Angiogenic ability detection: The angiogenic function of Se-CuSrHA@EGCG NPs was detected by tubule formation test, scratch healing test, real-time fluorescence quantitative PCR (qRT-PCR) and immunofluorescence staining. Figure 7 As shown, the results showed that Se-CuSrHA@EGCG NPs could promote tubule formation, endothelial cell migration, and upregulate angiogenic factors, indicating that it has good angiogenic ability.

[0054] Tubule formation assay: 100 μL of matrix gel (Corning, USA) was placed in a 48-well plate and incubated at 37°C for 30 min. Then human umbilical vein endothelial cells (HUVECs, 5×10 4 ) cells were inoculated into each well and incubated with Se-CuSrHA@EGCG extract for 6 h. The formation of tubules was observed under an inverted microscope, and the number of related structures was counted using Image J software. Figure 7 As shown in A, almost no tubule formation was observed in the control group. More tubules were observed in the Se-CuSrHA@EGCG group. Compared with the control group, more junctions and meshes appeared in the Se-CuSrHA@EGCG group.

[0055] Scratch healing assay: HUVECs (1×10 6 Cells / mL) were inoculated into 6-well plates. After cell confluence reached about 90%, a linear wound was made using a 10-μL pipette tip. The scratched suspended cells were rinsed, and the remaining cells were further cultured in Se-CuSrHA@EGCG extract containing 2% serum for 24 h. Finally, images of the migration area were recorded on a microscope, and the migration rate was analyzed by Image J software. Figure 7 As shown in B, compared with the control group, the migration area of ​​Se-CuSrHA@EGCG NPs increased and the mobility increased relatively.

[0056] qRT-PCR: The relative gene expression levels of angiogenic genes (CD31 and PDGF-B) were assessed in HUVECs using qRT-PCR. 5 The cells were placed in a 6-well plate and cultured with complete culture medium as control and Se-CuSrHA@EGCG extract for 7 days. Then, total RNA was extracted using Trizol reagent (Invitgen, USA) according to the instructions of RevertAid First Strand cDNA Synthesis Kit (Thermo FisherScience, USA). The gene expression of CD31 and PDGF-B was detected by Bio-Rad Thermal Cycler machine. Compared with the control group, CD31 increased significantly by 2.1 times in the Se-CuSrHA@EGCG group, and the expression level of PDGF-B also increased by about 1.5 times ( Figure 7 C). This indicates that Se-CuSrHA@EGCG can significantly promote the expression of vascular-related genes.

[0057] Immunofluorescence: HUVECs were seeded into a confocal culture dish (diameter = 15 mm) and the cells were incubated with the extract of Se-CuSrHA@EGCG NPs for 7 days. The subsequent operations were the same as step 13. Figure 7 As shown in (D), the fluorescence intensity of the Se-CuSrHA@EGCG group was higher than that of the control group, indicating that VEGF expression was upregulated, which may be attributed to the stimulatory effects of copper and strontium ions.

[0058] Step 15. Osteogenic ability detection: The osteogenic ability of Se-CuSrHA@EGCG NPs was detected by alkaline phosphatase (ALP) and alizarin red (ARS) staining, qRT-PCR and immunofluorescence staining. Figure 8 As shown, the results showed that the Se-CuSrHA@EGCG NPs group had more calcium matrix deposition and upregulated expression of osteogenic genes and osteogenic proteins, indicating that Se-CuSrHA@EGCG NPs can promote the osteogenic differentiation of periodontal ligament stem cells (hPDLSCs).

[0059] ALP and ARS: hPDLSCs from P3-P5 were cultured at 2×10 4 The cells were seeded at a density of 100 cells / well in a 24-well plate. After culturing for 24 hours, the original culture medium in the 24-well plate was aspirated, rinsed once with phosphate buffered saline (PBS), and PBS was discarded. 500 μL of osteogenic induction solution (10% FBS, 10 mM β-glycerophosphate, 1% Penicillin-Streptomycin, 0.1 μM dexamethasone, and 0.25 mM ascorbic acid) containing Se-CuSrHA@EGCGNPs (1 mg / mL) was added to each well to induce osteogenesis for 7 or 21 days. Then, 500 μL of 4 wt% paraformaldehyde solution was added to each well. After fixation for 15 minutes, 500 μL of ALP or ARS staining solution (pH = 8.3) was added to each well, protected from light, and incubated at 37°C for 30 minutes. Subsequently, the staining solution was discarded, and hPDLSCs were gently rinsed twice with PBS. The macroscopic effect of the well plate was photographed using a macro camera. The results are shown in the figure. Figure 8 As shown in A, the ALP staining and calcium nodule deposition of Se-CuSrHA@EGCG NPs were significantly deeper than those of the blank control group, which shows that Se-CuSrHA@EGCG NPs can effectively promote osteogenesis.

[0060] qRT-PCR and immunofluorescence: hPDLSCs (1×10 5Cells / mL) were seeded in 12-well plates and cultured in α-MEM complete medium for 12 h. Then, the medium was replaced with osteogenic induction solution containing Se-CuSrHA@EGCG NPs (1 mg / mL). After 7 days of culture, the expression levels of osteogenic genes (Runx2 and OCN) in hPDLSCs were evaluated by qRT-PCR, and immunofluorescence staining (RUNX2 and OPN) was performed. The specific operation steps are the same as step 12. As shown in 8B and C, compared with the control group, the expression of osteogenic genes and osteogenic proteins in the Se-CuSrHA@EGCG group increased, indicating that it has a good osteogenic effect.

Claims

1. A method for preparing an active element-doped sericin mineralized particle-loaded EGCG nanocomposite material, characterized in that: The following steps are involved: Step 1. extracting sericin to obtain sericin powder, and storing it at 4°C for later use; Step 2. Prepare a 10 wt% sericin solution: weigh 0.9-1.1 g of sericin prepared in step 1 and dissolve it in 9-11 mL of deionized water to obtain a sericin solution for later use; Step 3. Prepare the oil phase solution: add 2 mL of span80 into 98 mL of peanut oil and stir evenly using a high-speed homogenizer to obtain an oil phase emulsion; Step 4. Add the sericin solution in step 2 dropwise into the oil phase emulsion in step 3 being homogenized, and homogenize at 4000 rpm for 20 minutes to obtain a sericin mixed emulsion; Step 5. Add 2 mL of 25% glutaraldehyde crosslinking agent to the mixed emulsion obtained in step 4, and stir at 300 rpm for 2 hours to fully crosslink the Se NPs; Step 6. Suspend the solution obtained in step 5 into 300 mL of acetone solution and stir overnight to allow the particles to fully solidify; Step 7. After the mixed solution in step 6 is separated into layers, the white suspension layer is sucked out with a pipette, transferred to a new container, and washed with acetone for three times to obtain solidified sericin nanoparticles Se NPs; Step 8. Weigh 100 mg of the sericin nanoparticles Se NPs obtained in step 7, place in 100 mL of deionized water, stir evenly, add CaCl2 powder, SrCl2 powder and CuCl2 powder, stir at 150 rpm for 8 hours, maintain the temperature at 37°C, so that the metal ions in the solution are fully combined with Se NPs; the metal ions are Ca 2+ , Sr. 2+ and Cu 2+ ; Step 9. After the reaction in step 8 is completed, filter paper is used to remove excess unbound ions, and the precipitate obtained is resuspended in 100 mL, and 0.018-0.030 mol of Na3PO4 powder is added, and the pH is adjusted to 8.0 using sodium hydroxide solution; stirring is performed at 150 rpm for 8 hours, and aging, filtering, and washing are performed to obtain sericin-copper strontium modified hydroxyapatite nanoparticles Se-CuSrHANPs; Step 10. Prepare 20 mL of PEI / EGCG functional coating solution: 1 mg / mL EGCG solution and PEI solution dissolved in tris buffer solution were mixed in equal volumes to obtain a PEI / EGCG solution, wherein the concentration of the PEI solution was 2 mg / mL; Step 11. The Se-CuSrHA nanoparticles obtained in step 9 are placed in the PEI / EGCG solution of step 10, stirred at 37° C. for 4 hours to fully cross-link the molecules, and the unbound molecules are washed with deionized water and freeze-dried to obtain sericin mineralized particles loaded with EGCG nanocomposites Se-CuSrHA@EGCG NPs; Step 12. Characterization and detection of the sericin mineralized particles loaded with EGCG nanocomposite material Se-CuSrHA@EGCG.

2. The method for preparing the active element-doped sericin mineralized particles loaded with EGCG nanocomposite material according to claim 1, characterized in that: The specific operation of step 1 is as follows: weigh 9-11g of silk cocoons, cut them into pieces, wash them three times with deionized water, add them into 250mL of ultrapure water containing 2% w / v sodium carbonate, and heat and pressure at 120℃ for 30 minutes to remove silk fibroin; after completion, filter and collect the solution, and centrifuge at 3000rpm for 5 minutes; further dialyze for 48 hours to remove impurities, and change the solution every 8 hours; after the dialysis is completed, obtain sericin powder by freeze drying, and store it at 4℃ for future use.

3. The method for preparing the active element-doped sericin mineralized particles loaded with EGCG nanocomposite material according to claim 1, characterized in that: The specific operation of step 8 is as follows: the amount of the CaCl2 powder is 0.024-0.040 mol, the amount of the SrCl2 powder is 0.003-0.005 mol, and the amount of the CuCl2 powder is 0.003-0.005 mol.

Citation Information

Patent Citations

  • A method for preparing hydroxyapatite / serine protein hybrid microcapsules

    CN104826563B

  • Metal organic coordination polymer coated natural sericin microsphere as well as preparation method and application thereof

    CN108653741A

  • Preparation method of sericin-hydroxyapatite / sodium alginate drug-loaded microspheres

    CN116999617A